Noninherited Risk Factors of Congenital Heart Defects in Offspring: A Revi (Bangladesh Journal of Child Health, 2017)
Prognosis of children with congenital heart defects (CHDs) continues to improve with advancement in technology and training in pediatric cardiology and cardiac surgery; however, lack of information about risk factors for malformations in cardiovascular development impeded the prevention of CHDs. Etiology of CHDs are complex and possibly lies within the interaction of environmental exposures and inherited factors. Studies found multiple maternal environmental exposures, including living in newly renovated rooms, residential proximity to main traffic, smoking and maternal occupation as manual worker significantly associated with CHDs. Advanced maternal age, low socioeconomic status, maternal perinatal diseases including maternal fever, diabetes, influenza, maternal certain medication use and alcohol intake were also significantly associated with CHDs. Isolated CHDs and multiple defects have different profiles of risk factors, while subtype of CHDs share common risk factors. Because of differences in methods, these studies are only suggestive. Relatively less information has been reported on noninherited factors that may have an adverse effect on the cardiovascular development, which has made it difficult to create population-based strategies to reduce the burden of illness from CHDs and for couples to choose lifestyles to reduce the risk of delivering a child with CHDs.Bangladesh J Child Health 2017; VOL 41 (1) :40-52